Influence of consumption of probiotics on presence of enterobacteria in the oral cavity - Leão, Mariella Vieira Pereira; Cassia, Ricardo Coelho; dos Santos, Silvana Soléo Ferreira; Silva, Célia Regina Gonçalves; Jorge, Antônio Olavo Cardoso [UNESP] (FapUNIFESP (SciELO), 2011)
Clinical benefits of probiotics have been clearly reported in different gastrointestinal disorders, many of them caused by enterobacteria. The oral cavity is a port of entry and can be an important reservoir of these microorganisms. This work evaluated whether consumption of probiotics was able to influence the presence of enterobacteria in the oral cavity and the specific secretory response against these microorganisms. Saliva samples of healthy individuals were collected and plated in Mac-Conkey agar. Carriers of Gram-negative, rod-shaped microorganisms in the oral cavity were selected and instructed to use the probiotic Yakult LB for 20 days. Saliva was then collected and enterobacteria species were identified using the API 20 E system and by ELISA using anti-enterobacteria IgA. The results showed reduction in the prevalence of enterobacteria, but no significant changes in enterobacterial counts (log CFU/ mL; p = 0.3457). The species most frequently isolated were Enterobacter cloacae and Klebsiella oxytoca, both before and after probiotic consumption. No significant changes were observed in anti-enterobacteria IgA levels. In conclusion, probiotic consumption had some influence on enterobacterial presence in the oral cavity, but did not affect enterobacterial counts or the specific immune secretory response against them.
Keywords: Bifidobacterium; Enterobacteriaceae; Lactobacillus casei; Probiotics